Development of green hygienic coating based on essential oil microcapsules - Bogdan, Sofía (2016)
The challenges for developing new materials are accomplishing more functionality with less material due to the increasing efficiencies of the smart approaches. In this sense, the coating technology based on the incorporation of microcapsules has emerged recently as a strategy in the advance of protective and functional materials, promising an environmentally friendly approach. Microbial colonization of painted surfaces is a major concern because it shortened the useful life of the coating by discoloration and degradation. Besides there is a great concern about the indoor microbial colonization especially in places that should have high standards of environmental hygiene as in the food industry and those related to human health-care. The aim of this work is to develop a novel green antifungal water-borne paint formulated with melamine-formaldehyde (MF) microcapsules containing essentials oil as biocide agent. The microcapsules were synthesized by interfacial polymerization. Melamine-formaldehyde resin was used for the microcapsule shell wall, and two different essential oils (EOs) as core materials. The EOs studied were Tea Tree and Lavandin Abrialis. Microcapsule morphology was examined by Field-Emission Scanning Electron Microscopy (FE-SEM), while their size distributions were determined by light diffraction (LD). Microcapsule composition (shell and core) was analyzed by FTIR-ATR spectroscopy. Preparation of acrylic water-borne paint was done in a high speed disperser. The microcapsules (MF-Tea tree and MFLavandin) were incorporated into the original paint just before used, at 6% by weight of the total paint composition. As negative control a paint without biocide was used. The effectiveness of these microcapsules on paint film was evaluated by plaque inhibition assay. Commercial gypsum boards were used as substrate. Each painted panel was inoculated with 100 μl of the spore suspension of Aspergillus sp. and kept in a culture chamber at 86% relative humidity for 4 weeks. The fungal growth was estimated as a percentage of coverage onto the surface and scored according to ASTM D5590 standard specification. The results obtained in antifungal assay on paint film were promising. According to ASTM D5590, the score obtained by MF-lavandin paint was 1, which indicate just a trace growth onto the painted surface (<10%). On the other hand, the control and MF-Tea tree paints obtained the same score: 4 points, the highest qualification (fungal growth >70%). Comparing those results, it can be seen that Aspergillus sp. growth reduction was significant when MF-lavandin paint was used, suggesting that those microcapsules had an inhibitive activity on the dry film whereas MF-Tea tree had not such activity.